Talking Stick Model, Students Activities and Learning Result in Economic Business Student - Pradana, Daniel Gusti (Classroom Action Research Journal (CARJO), 2018)
Learning has applied cooperative learning with the aim that students can pay attention when teachers explain the material. But in reality in the classroom, when the teacher explained the students' learning is still not optimal in following the lesson. Many students speak for themselves, drowsy and unfocused in watching lessons. Researchers in this case choose the learning model Talking stick to overcome learning problems. This model was chosen as an action in this study, because the Talking stick model stimulates the student learning process. It can be concluded this research aims to improve students' activity and learning outcomes by using Talking stick learning model. The type of research used is Classroom Action Research (PTK) with qualitative descriptive approach. Application of learning model Talking stick improves the activity and student learning outcomes, it is shown in the percentage of student activeness in cycle I and cycle II has increased, the cycle I the percentage of students activeness get 55.20% and in cycle II the percentage of students activeness gained 62.42% . The improvement of students' activity after applying the talking stick learning model is 7.22%. Student learning outcomes also experienced an increase of 4.41 which can be seen from the average overall learning outcomes, on the first cycle average learning outcome is 78.60 to 83.01 in cycle II.